2017
DOI: 10.1200/jco.2017.35.15_suppl.9507
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nivolumab (NIVO) plus ipilimumab (IPI) in patients with melanoma (MEL) metastatic to the brain: Results of the phase II study CheckMate 204.

Abstract: 9507 Background: Brain metastases (BMts) are a major cause of morbidity/death in MEL. We report the first efficacy data in MEL patients (pts) with BMts who received NIVO+IPI in study CheckMate 204. Methods: In this multicenter US trial (NCT02320058), MEL pts with ≥1 measurable BMt 0.5-3.0 cm and no neurologic symptoms or steroid Rx received NIVO 1 mg/kg + IPI 3 mg/kg Q3W x 4, then NIVO 3 mg/kg Q2W until progression or toxicity. Pts with severe adverse events (AEs) during NIVO+IPI could receive NIVO when toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 0 publications
3
72
0
1
Order By: Relevance
“…1C). Thus, the outcome of anti-PD-1/anti-CTLA-4 combination therapy was superior to the two monotherapies, which is in line with the reported intracranial response rate for anti-PD-1 monotherapy (21-25%) (12)(13)(14)(15) and anti-PD-1/anti-CTLA-4 combination therapy (50-55%) (15,16), as well as the 6 month progression-free survival rate of 28% and 46%, respectively (15). Due to these promising data, we focused on the anti-PD-1/anti-CTLA-4 combination therapy.…”
Section: The Presence Of Extracranial Tumor Is Critical For Intracransupporting
confidence: 82%
See 1 more Smart Citation
“…1C). Thus, the outcome of anti-PD-1/anti-CTLA-4 combination therapy was superior to the two monotherapies, which is in line with the reported intracranial response rate for anti-PD-1 monotherapy (21-25%) (12)(13)(14)(15) and anti-PD-1/anti-CTLA-4 combination therapy (50-55%) (15,16), as well as the 6 month progression-free survival rate of 28% and 46%, respectively (15). Due to these promising data, we focused on the anti-PD-1/anti-CTLA-4 combination therapy.…”
Section: The Presence Of Extracranial Tumor Is Critical For Intracransupporting
confidence: 82%
“…Pembrolizumab and nivolumab also showed efficacy in melanoma BrM with an ~21% response rate in the brain (12)(13)(14)(15). A very recent interim analyses from two clinical trials in drug-treatment naïve patients with melanoma BrM (ABC trial (15) and CheckMate 204 trial (16)) reported a 50% and 55%…”
Section: Introductionmentioning
confidence: 99%
“…The activity of nivolumab plus ipilimumab continues to be evaluated in phase 2 studies, including the anti–PD-1 Brain Collaboration Trial (NCT02374242) and the CheckMate 204 study of the combination in patients with melanoma brain metastases. 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…Relevant reduction in brain metastases was observed in 28% of patients, warranting further investigation of ICBs in this patient population [109]. In the phase 2 CheckMate 204 study, the combination of nivolumab and ipilimumab was administered to 75 patients with advanced melanoma and untreated brain metastases, and provided an intracranial ORR of 55% and an extracranial ORR of 49% [110].…”
Section: Immunotherapeutics and Patient Selectionmentioning
confidence: 99%